An Example of Imaging Deeper using Extended Vibroseis Cross-Correlation. Issue 1 (1st December 2016) - Costelloe, Ross D.
Abstract : Geoscience Australia has been collecting Vibroseis deep crustal reflection seismic data since 1999. Since 2013, Geoscience Australia has also collected the uncorrelated single sweep data for each VP of each survey. For a typical survey using three 12 s sweeps, each with 20 s listening time, this means collecting 96 s + 20 s = 116 s of data per VP, instead of 20 s of data per VP. This is nearly a 6-fold increase in data volume, and has been made possible by the availability of high capacity USB data disks. Using extended cross-correlation on the uncorrelated record data, it is possible to image deeper into the earth than using standard vibroseis cross-correlation. Geoscience Australia applied the method of truncated cross-correlation to a deep crustal reflection seismic survey collected over the Yathong Trough section of the Darling Basin in central NSW in 2013. This area showed unusual reflectivity below the Moho in the mantle, stimulating this study. The extended correlation stack showed some faint reflectivity visible from 18s to 24 s which may link to a region of higher reflectivity visible at about 18s in the mantle. Also, the truncated extended cross-correlation method appeared to show improved reflectivity in the mid to lower crustal areas.